Feasibility of TEMPO-functionalized imidazolium, ammonium and pyridinium salts as redox-active carriers in ethaline deep eutectic solvent for energy storage. Issue 6 (30th June 2020) - Chen, Brian; Mitchell, Sarah; Sinclair, Nicholas; Wainright, Jesse; Pentzer, Emily; Gurkan, Burcu
Abstract : Design and considerations for all organic, redox-active, deep eutectic solvents for energy storage. Abstract : The discovery of electrolytes that have low vapor pressures and high solubility towards redox active species with an ability to undergo multiple electron transfer reactions is a challenge to realize in large-scale energy storage. Herein, we investigate the feasibility of (2, 2, 6, 6-tetramethylpiperidin-1-yl)oxyl (TEMPO) derived halide salts as redox active species in ethaline (1 : 2 ethylene glycol : choline chloride), a deep eutectic solvent (DES). Hydrogen bonding and electrostatic interactions achieved by the functionalization of TEMPO are shown to improve solubility in ethaline. This is the first study evaluating the physical properties and electrochemical behavior of the newly synthesized TEMPO-salts in ethaline providing insight into the impact of chemical functionality on the utility of these redox active species in DESs.